Identification of Flora and Life Forms of Plants in Kandovan (East Azarbaijan) - Zh. Toupcvhi (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2011)
Kandovan is located in the north west of Iran in the province of east Azarbaijan. Its geographical position is 46ْ 10′ to 46 ْ 20َ and 37 ْ 42َto 37 ْ 52َ. This survey carried out at elevations of 1800-3200 m from sea level. The aim of this project was the collection and identification of plants grown in its 7000 hectares of range land. During two seasons about 400 plant samples were collected and identified in herbarium. In this project 256 species were identified to belong to 153 genus and 37 families. The most important plants families that collected in this region belonged to Asteraceae, Fabaceae, Lamiaceae, Brassicaceae and Apiaceae. Asteraceae (40 species), Fabaceae (29 species), Lamiaceae (25 species), Brassicaceae (22 species) and Apiaceae (16 species) were the dominant species in the area, respectively. The life forms of these species were determined by using of Raunkierُs method and they consist of 58.20% Hemicryptophytes, 30.07% Therophytes, 1.17% Phanerophytes, 5.85% Chamaephytes and 4.68% Geophytes.